Gender differences in accepting and receiving requests for tasks with low promotability - Babcock, Linda; Recalde, Maria P; Vesterlund, Lise; Weingart, Laurie (The American economic review, 2017)
Gender differences in task allocations may sustain vertical gender segregation in labor markets. We examine the allocation of a task that everyone prefers be completed by someone else (writing a report, serving on a committee, etc.) and find evidence that women, more than men, volunteer, are asked to volunteer, and accept requests to volunteer for such tasks. Beliefs that women, more than men, say yes to tasks with low promotability appear as an important driver of these differences. If women hold tasks that are less promotable than those held by men, then women will progress more slowly in organizations.